The application of the EN ISO 52016 standard and its Italian National Annex to assess the heating and cooling needs of a reference office building - Bianco Mauthe Degerfeld Franz (EDP Sciences, 2021)
The EN ISO 52016-1 standard presents a new simplified dynamic calculation procedure, whose aim is to provide an accurate energy performance assessment without excessively increasing the number of data required. The Italian National Annex to EN ISO 52016-1, currently under development, provides some improvements to the hourly calculation method; despite many works can be found in literature on the hourly model of EN ISO 52016-1, the National Annexes application has not been sufficiently analysed yet. The aim of the present work is to assess the main improvements introduced by the Italian National Annex and to compare the main results, in terms of energy need for space heating and cooling. To this purpose, an existing building representative of the Italian office building stock in Northern Italy was selected as a case study. The energy simulations were carried out considering both continuous and reduced operation of the HVAC systems. The options specified in the Italian National Annex were firstly applied one by one, and then all together. The variation of the energy need compared to the international base procedure is finally quantified. For the premises and the scope above discussed, the present work is intended to enhance the standardisation activity towards the adoption of more accurate and trustable calculation methods of the building energy performance.